The influence of Portuguese on Amazonian French Creole lexicon - Ferreira, Jo-Anne S. (John Benjamins, 2017)
This paper focuses on Kheuól, an Amazonian French Creole variety spoken by the Karipúna and Galibi-Marwono in northern Amapá, Brazil. The paper will examine the nature and degree of the contact between French Creole and Portuguese on the Oiapoque River Border, and on the resulting Portuguese influence on Kheuól lexicon at present. As the official language of Brazil, Portuguese remains the prestige language, and continues to dominate the educational system, religion and trade in the Oiapoque area of Uaçá, northern Amapá (Tassinari 2003). Data sources include three bilingual French Creole-Portuguese dictionaries, two published (Tobler 1987 and Picanço Montejo 1988) and one unpublished (Corrêa and Corrêa1998), as well as interviews with speakers.
Some preliminary observations